The Paradox of Digital Financial Inclusion: Unpacking the Alternative Credit Scoring Gap for MSMEs in FinTech Lending - Busrin Raihana Mas'ud; Fadlina; Kurniawan; Alliah Grace D. Gubangco (Universitas Sulawesi Barat, 2026)
FinTech lending utilizes alternative credit scoring (ACS) based on digital footprints to expand financial inclusion for Micro, Small, and Medium Enterprises (MSMEs). However, this approach risks excluding marginalized MSMEs that lack extensive digital data. This study explores the paradoxical digital divide in MSME credit assessment and examines the potential of Accounting Information Systems (AIS) to bridge this gap. Employing a descriptive-exploratory qualitative approach, multiple case studies were conducted involving 15 MSME actors with varying digitalization levels in Parepare City, Indonesia. The findings reveal a